2012
DOI: 10.1111/j.1399-0039.2012.01845.x
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐locus HLA class I and II allele and haplotype associations with follicular lymphoma

Abstract: Follicular lymphoma (FL) is an indolent, sometimes fatal disease characterized by recurrence at progressively shorter intervals and is frequently refractive to therapy. Genome-wide association studies have identified SNPs in the human leukocyte antigen (HLA) region on chromosome 6p21.32–33 that are statistically significantly associated with FL risk. Low to medium resolution typing of single or multiple HLA genes has provided an incomplete picture of the total genetic risk imparted by this highly variable regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 26 publications
2
47
0
1
Order By: Relevance
“…Here and in Table 3: level of statistical significance (after Bonferroni correction for multiple comparisons). studies involving other population groups, this locus showed an association with a lower risk of follicular lymphoma [4,9,12] and increased risk of marginal cell lymphoma [12], but not with the risk of diffuse large cell lymphoma [12]. The infl uence of rs2647012 on the increase in the risk of these lymphomas in Western Siberia can be caused by a not identifi ed factor.…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…Here and in Table 3: level of statistical significance (after Bonferroni correction for multiple comparisons). studies involving other population groups, this locus showed an association with a lower risk of follicular lymphoma [4,9,12] and increased risk of marginal cell lymphoma [12], but not with the risk of diffuse large cell lymphoma [12]. The infl uence of rs2647012 on the increase in the risk of these lymphomas in Western Siberia can be caused by a not identifi ed factor.…”
Section: Resultsmentioning
confidence: 83%
“…This means that if the effect of nucleotide substitution is less pronounced, the association could remain undetected. In the work [12], locus rs2647012 reduced the risk for follicular lymphoma in 1.42 times, and in the studies [4,9] -1.8 times. The size of the group should be >70 subjects in order to reach 80% statistical power to detect such effect.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…In an international alpha-trial testing of 20 blinded samples, the 454 Life Sciences GS FLX System sequencing method demonstrated 98 % concordance with known genotypes between eight participating labs [2]. In our other studies, using at least one control per PTP region per run, 100 % of control sample genotypes (previously characterized by Sanger Sequencing with ambiguity reduction) were concordant [4, 5]. The average rate of detection of novel alleles was ~0.04 % (8/19,069 loci) in Caucasoid study populations [4, 5].…”
Section: Introductionmentioning
confidence: 86%